E-Wallets and Zakat: Opportunities and Challenges of Sharia Financial Technology in Enhancing the Financial Well-Being of the Madura Community - Qadariyah, Lailatul; Fadhil, Fakhry; Adinata, Uslan; Wong, Lucas; Dara, Ravi (STAI Publisistik Thawalib Jakarta, 2026)
The adoption of e-wallets for zakat payments remains low due to limited digital literacy, security concerns, and the requirement for Sharia compliance, despite fintech innovations improving efficiency and transparency. This study investigates the influence of opportunities and challenges in e-wallet usage on community participation in digital zakat payments. A mixed-methods approach with a Sequential Explanatory design was employed. The quantitative phase used a correlational approach with questionnaires, analyzed in SPSS for descriptive statistics, and tested for validity, reliability, normality, and linearity, using t-tests and F-tests. The qualitative phase involved a case study with interviews and documentation from 20 informants over 59 days, analyzed through data condensation, descriptive presentation, and triangulation of sources and techniques. Results indicate moderately high perceptions of e-wallet opportunities (mean = 16.00), high perceived challenges (mean = 36.10), and moderately high zakat usage (mean = 16.43). Statistical analyses confirmed significant positive relationships between variables. The Madura community, especially younger generations, uses M-Banking and ShopeePay for daily transactions, including zakat, although most still prefer cash. E-wallets provide accessibility, flexibility, and transactional proof, but limited knowledge, security concerns, and traditional habits limit their adoption for zakat payments. The study concludes that opportunities enhance zakat participation, challenges reduce interest, and overall adoption depends on community understanding, access, and trust. This research offers important insights into how e-wallet opportunities and challenges affect the effectiveness of digital zakat payments.